Corporate Social Responsibility in Resource Exploitation Towards Achieving Sustainable Development Goals (SDGs) - Shahan, Akbar Helmie Nur; Naftalie, Livia Aurelia; Putra, Moody Rizqy Syailendra (Journal of Health Education Law Information and Humanities, 2025)
This research aims to analyze the importance of Sustainable Development Goals (hereinafter referred to as “SDGs”) in correlation to Indonesia’s use of natural resources. This analysis is conducted by examining the living conditions in Indonesia, and the indicator of SDGs relating to poverty and the major problem of overconsumption of natural resources. This research is proposed to devote to the development of understanding what factors need to be fulfilled to obtain SDGs, as well as providing better information about the conditions of our natural resources and how it is being used. The outcome of this research is anticipated to provision a significant knowledge  about the importance of SDGs in Indonesia’s civil code and different aspects on how to meet the SDGs. With the fulfillment of SDGs in Indonesia, this can lead to a better reinforcement of the legal framework that helps sustainable development that can help the society in every sector.